Optimization of projection schemes of digitization of ill-posed problems - Solodkii, S. G. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We construct new projection schemes of digitization of ill-posed problems, which are optimal in the sense of the amount of discrete information used. We establish that the application of self-adjoint projection schemes to digitization of equations with self-adjoint operators is not optimal.